Integrating The History of Mathematics in Secondary Classrooms: A Practical Pedagogical Approach - Zhou Yini (IKIP Siliwangi, 2026)
Despite extensive theoretical recognition of the History of Mathematics (HPM) in enhancing mathematics education, a persistent gap remains between scholarly advocacy and classroom implementation in Chinese secondary schools. This study aims to bridge this theory-practice divide by investigating the status of HPM integration and proposing actionable pedagogical strategies. A mixed-methods approach was employed, combining a questionnaire survey of 285 students across three grades and semi-structured interviews with all 26 mathematics teachers at Chongxian Middle School in Yongchun County, Fujian Province. Quantitative data were analyzed using SPSS to examine student attitudes and knowledge acquisition, while qualitative interview data revealed teachers' self-reported familiarity with historical content (only 7.8%